Serologic and Urinary PCR Survey of Leptospirosis in Healthy Cats and in Cats with Kidney Disease. (13th January 2014) - Rodriguez, J.; Blais, M.‐C.; Lapointe, C.; Arsenault, J.; Carioto, L.; Harel, J.
<x xml:space="preserve">Abstract</x> Background Although there is serologic evidence of exposure of cats to Leptospira spp., clinical disease is rarely reported in cats. Objective To compare the seropositivity and urinary polymerase chain reaction (PCR) status for Leptospira spp. between healthy (H) cats and cats with kidney disease (KD), to investigate the serovars potentially involved, and to evaluate potential risk factors. Animals Two hundred and forty client‐owned cats. Methods Cats were prospectively recruited and classified based on physical examination, complete blood count, serum biochemistry profile, and urinalysis (125 H and 115 KD cats). Leptospira spp. serology (titers ≥1 : 100 considered positive) and urinary PCR were performed in all cats. Data assessing risk factors, obtained from a questionnaire, were evaluated using logistic regression models. Results Seropositivity for Leptospira spp. was statistically different between groups: 7.2% (9/125) and 14.9% (17/114) in the H and KD, respectively (P = .05). The proportion of PCR‐positive cats was not. The most common serovars detected serologically were Pomona (n = 16) and Bratislava (n = 8). Risk factors for seropositivity included outdoor and hunting lifestyles (P = .03 and P < .001, respectively), the presence of another cat in the household (P < .01), and the sampling period, with the greatest number of cases identified between June and August (P =.02). Conclusions Seropositivity was significantly greater in KD cats, suggesting that the role of Leptospira spp. in KD in cats should be further investigated. The detection of urinary shedding of leptospires in several cats identifies a potential role in the transmission of the organism.